n vivo antiulcer activity of the aqueous extract of Bauhinia purpurea leaf. - Zakaria, Zainul Amiruddin; Abdul Hisam, E. E.; Rofiee, M. S.; Mohtarrudin, Norhafizah; Somchit, Muhammad Nazrul; Teh, L. K.; Salleh, M. Z. (Elsevier, 2011)
Ethnopharmacological relevance Bauhinia purpurea (Fabaceae) is a medicinal plant traditionally used to treat various ailments, including ulcers. In order to establish pharmacological properties of the leaf of Bauhinia purpurea, studies were performed on antiulcer activity of the plant's aqueous extract.